Nososticta impercepta sp. nov. (Odonata: Platycnemididae) from Timor, with a key to the Sundaic species - Seehausen, Malte; Theischinger, Günther (Zootaxa, 2017)
Nososticta impercepta sp. nov. is described and illustrated (holotype ♂: 28.vi.1911, Niki-Niki [South Central Timor Regency], Timor, Indonesia, C.B. Haniel leg., Coll. Ris, No. 2477; deposited at the Forschungsinstitut und Naturmuseum Senckenberg, Frankfurt am Main, Germany). An illustrated key for the species of Nososticta known from the Lesser Sunda Islands is given. The occurrence of N. selysi in Timor is considered to be doubtful. Nososticta emphyla is newly recorded from Sumbawa Island.